STRATEGI GURU DALAM MENGEMBANGKAN KETERAMPILAN MENULIS DAN LITERASI ISLAMI SISWA DI TADIKA ANAKKU SHOLEH - Fauziah Sinaga, Silvi; Mavianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe teacher strategies in developing writing skills and Islamic literacy for students aged 5–6 years at Tadika Anakku Sholeh, Selangor, Malaysia. A qualitative descriptive approach was employed with data collected through observation of 12 learning sessions, in-depth interviews with the principal and three classroom teachers, and documentation analysis of 15 students' writing products. Data were analyzed using Miles and Huberman's interactive model. Findings reveal that teachers consistently applied basic Islamic writing strategies hijaiyah letters, Islamic words (Allah SWT, Prophet), and daily prayers with 100% frequency. However, creative strategies such as game-based writing and copying short verses were only implemented by 33% of teachers, indicating varying adaptive capacities. Students' writing skills achieved